EFEKTIVITAS MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN LEMBAR KERJA PESERTA DIDIK INTERAKTIF UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS VII SMPN 23 MATARAM TAHUN AJARAN 2023/2024 - Bay, Rani Laksmi; Nani Kurniati; Ulfa Lu'luilmaknun; Syahrul Azmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problem in this research is the low problem-solving ability of grade VII students of SMPN 23 Mataram. This research aimed to determine the effectiveness of the Problem Based Learning (PBL) model assisted interactive Student Worksheet (LKPD) to improve the mathematical problem solving skills of grade VII students. This research is a quasi-experimental with Posttets-Only Control Design. The population and samples of this research are all grade VII student. The instruments used are RPP, interactive LKPD, Posttets questions and observation sheets for teacher and student activities. The data are already normally distributed and the variance is homogeneous. Then a t test was carried out using polled variance which showed that there was a difference in the average problem-solving ability between the experimental class and the control class. In addition, the average score of the experimental class was higher than the average score of the control class. Thus, it can be concluded that the Problem Based Learning (PBL) model assisted interactive LKPD is effective in improving the mathematical problem solving skills of grade VII students of SMPN 23 Mataram.